PENGGUNAAN MEDIA PAPAN MENARA BUDAYA DALAM MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPAS SISWA KELAS IV B DI SDN KEBONSARI 1 SURABAYA - Tsalasah Alfirdausi Zahrah; Delia Indrawati; Ganda Riswanto; Sri Yuniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the effectiveness of using cultural tower board media in improving the learning outcomes of Natural and Social Sciences (IPAS) for class IV B students at SDN Kebonsari 1 Surabaya. The cultural tower board media was chosen as a learning tool because it has the potential to make the learning process more interesting, interactive and meaningful for students. The method used in this research is Classroom Action Research (PTK) which is carried out in two cycles, with each cycle consisting of planning, implementation, observation and reflection stages. The subjects of this research were class IV B students at SDN Kebonsari 1 in Surabaya City. Data was collected through learning results tests and observations, to measure student responses to the use of cultural tower board media. The research results showed a significant increase in student learning outcomes from cycle I to cycle II. The average student learning test score increased from 62.18 in cycle I to 87.2 in cycle II. Apart from that, student activity and participation in learning has also increased, as can be seen from the results of observations which show an increase in student activity and cooperation. Student responses to the use of cultural tower board media were also very positive. Most students stated that this media made learning more interesting and easier to understand. Thus, the use of cultural tower board media can be an effective alternative in improving science and science learning outcomes for class IV B students.